1989
DOI: 10.1021/ic00302a006
|View full text |Cite
|
Sign up to set email alerts
|

Chromium, molybdenum, and tungsten zerovalent complexes of the nitrogen chelating ligand 2-(phenylazo)pyridine (2-PAP), including air-stable cis-M(CO)2(2-PAP)2 and M(2-PAP)3

Abstract: Equimolar reaction of the title ligand (II) with the (norbornadiene)tetracarbonyls (I) results in the formation of the monosubstitution products (III).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…However, three successive one-electron-transfer processes were observed in our experimental conditions. Notably, the ligand reductions in the tris-chelate 2 were systematically cathodic 10 as compared to those in [Cr(pap) 3 ]. This may be attributed to the strong inductive effect of p-NH(Ar) substitution in 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, three successive one-electron-transfer processes were observed in our experimental conditions. Notably, the ligand reductions in the tris-chelate 2 were systematically cathodic 10 as compared to those in [Cr(pap) 3 ]. This may be attributed to the strong inductive effect of p-NH(Ar) substitution in 2.…”
Section: Resultsmentioning
confidence: 99%
“…Herein we describe the synthesis and properties of a series of chromium(II) and chromium(III) complexes of the isomeric 2-[( N -arylamino)phenylazo]pyridine ligands. Optical properties of these are markedly different than those of the parent chromium−pap complexes, which are highlighted in this paper.…”
Section: Introductionmentioning
confidence: 85%
“…As the copper(II) ion in a octahedral geometry exhibits Jahn–Teller distortion, generation of tris complexes of copper(II) ion with bidentate ligands is a challenge to synthetic inorganic chemists. Moreover, tris complexes of transition metal ions with abpy, one of the stronger π acidic bidentate and bridging ligands, are limited, while tris(bpy) and tris(2-phenylazopyridine) complexes are numerous. So far only a tris(abpy) complex of ruthenium(II) ion of type [Ru(abpy) 3 ] 2+ has been reported in literature .…”
Section: Introductionmentioning
confidence: 99%
“…1) system have been undertaken and a number of studies of metal complexes containing this type of ligand have been reported. These include investigations of complexes of Fe(II) [1,2], Ni(II) [2], Hg(II) [3,4], Os(II) [5,6], Ru(II) [7][8][9][10][11][12][13][14][15][16][17][18][19], Cr(0), Mo(0), W(0) [20,21], Cr(II) [22], Cu(I) [23], Rh(III) [24,25], Rh(I) [26], Ag(I) [27], Re(III) [28], Co(II) [29], Mo(IV) [15], Ru(III) [30], Sn(IV) [31] and organometallic complexes of Re(I) [32] and Sn(IV) [33][34][35][36][37]. In spite of such a wide-ranging series of studies on a variety of metal complexes involving these ligands, the structures of the mer-0277-5387/$ -see front matter Ó 2004 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%